A comparative sudy of two pressure relieving techniques on three different wheelchair cushions - C. Eksteen; P. Cilliers; A. Swanepoel; E. Vermaak; Q Trollip; T. Wilford; P. M. van Dyk (AOSIS, 2006)
Introduction: Pressure relief done by a spinal cord injured patient is of utmost importance in order to prevent pressure sore formation. Some pressure-relieving techniques are described in previous literature, but their effectivity has not yet been deter- mined on different wheelchair cushions. Null Hypothesis (H0): The null hypothesis (H0) stated for thi study is that there is no difference in the effectivity of forward leaning and forward leaning towards the left as pressure relieving techniques for quadriplegic wheelchair users over the differen wheelchair cushions. Design: An analytical experimental study design using a convenient sample group of ten complete lesion quadriplegics (C6 to T1) was performed at the Physiotherapy Department, University of Pretoria. Method: Interface pressure (in mmHg) over the ischial tuberosities and upper thigh areas was measured using the Talley Oxford Pressure Monitor MKII with a 12-way matrix cell system. Results and Conclusion: The Friedman test for associated observations indicated statistically that the leaning  diagonally forward pressure relieving technique is more effective for all three wheelchair cushions used in this study.